Synergistic and Antagonistic Effects of Sodium Molybdate-Zn2+ System - J. Wilson Sahayaraj; A. John Amalraj; Susai Rajendran; N. Vijaya (E-Journal of Chemistry)
The inhibition efficiency (IE) of sodium molybdate (SM) in controlling corrosion of carbon steel in an aqueous solution containing 120 ppm of Cl-, in the absence and presence of Zn2+ has been evaluated by weight-loss method. A synergistic effect exists between SM and Zn2+ when the concentration of Zn2+ is 25 ppm and above. Inhibition efficiencies obtained are greater than 85%. Antagonistic effect exists between SM and Zn2+ when the concentration of Zn2+ is 10 ppm and below. The SM-Zn2+ system shows excellent IE up to third day. Above third day IE decreases. Acceleration of corrosion takes place. Excellent IE is shown at pH 5,7 and 12. At pH 9, IE decreases since Zn2+ is precipitated as Zn(OH)2 in the bulk of the solution. Polarization study reveals that SM-Zn2+ system functions as a mixed inhibitor. FTIR spectra reveal that the protective film consists of Fe2+-SM complex and Zn(OH)2.